Therapeutic targeting of STAT3 (signal transducers and activators of transcription 3) pathway inhibits experimental autoimmune uveitis. - Cheng-Rong Yu; Yun Sang Lee; Rashid M Mahdi; Narayanan Surendran; Charles E Egwuagu (PLoS ONE)
Mice with targeted deletion of STAT3 in CD4(+) T-cells do not develop experimental autoimmune uveitis (EAU) or experimental autoimmune encephalomyelitis (EAE), in part, because they cannot generate pathogenic Th17 cells. In this study, we have used ORLL-NIH001, a small synthetic compound that inhibits transcriptional activity of STAT3, to ameliorate EAU, an animal model of human posterior uveitis. We show that by attenuating inflammatory properties of uveitogenic lymphocytes, ORLL-NIH001 inhibited the recruitment of inflammatory cells into the retina during EAU and prevented the massive destruction of the neuroretina caused by pro-inflammatory cytokines produced by the autoreactive lymphocytes. Decrease in disease severity observed in ORLL-NIH001-treated mice, correlated with the down-regulation of α4β1 and α4β7 integrin activation and marked reduction of CCR6 and CXCR3 expression, providing a mechanism by which ORLL-NIH001 mitigated EAU. Furthermore, we show that ORLL-NIH001 inhibited the expansion of human Th17 cells, underscoring its potential as a drug for the treatment of human uveitis. Two synthetic molecules that target the Th17 lineage transcription factors, RORγt and RORα, have recently been suggested as potential drugs for inhibiting Th17 development and treating CNS inflammatory diseases. However, inhibiting STAT3 pathways completely blocks Th17 development, as well as, prevents trafficking of inflammatory cells into CNS tissues, making STAT3 a more attractive therapeutic target. Thus, use of ORLL-NIH001 to target the STAT3 transcription factor, thereby antagonizing Th17 expansion and expression of proteins that mediate T cell chemotaxis, provides an attractive new therapeutic approach for treatment of posterior uveitis and other CNS autoimmune diseases mediated by Th17 cells.